Development of a low-power smart water meter for discharges in Indus Basin irrigation networks - Ahmad, Z.; Asad, E.U.; Muhammad, A.; Ahmad, Waqas; Anwar, Arif A. (2013)
To improve the sampling frequency of water diversion to distributary canals and to improve equity of distribution and data handling we have developed a smart electronic water meter based on ultrasonic sensors and GPRS modem to frequently record and transmit the water diversion data to a centralized server. The server processes the data to extract useful information for example seasonal cumulative water deliveries and discharge time series. The Wireless Sensor Node (WSN) inspired design is extremely low-power, field deployable and scalable with respect to cost and numbers. This paper, reports the first steps towards practical realization of a smart water grid in the Indus river basin, conceptualized by the authors in previous theoretical studies.